2019
DOI: 10.1016/j.gendis.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D level and vitamin D receptor gene polymorphism as a risk factor for congenital heart diseases in offspring; An Egyptian case-control study

Abstract: Vitamin D & vitamin D receptor (VDR) signaling play a very crucial role in early embryonic heart development. We construct this case-control study to investigate the association between maternal serum vitamin D level & VDR gene Fok1 polymorphism and risk of congenital heart defects (CHD) in offspring. Fifty mothers who had term neonates with CHD were considered as cases. Fifty age-comparable healthy mothers who had neonates without CHD were contemplated as controls. Maternal serum 25 hydroxyvitamin D [25(OH) D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…In a study conducted in Zakazig University, Egypt by Mokhtar et al they analyzed the association between both maternal VD level and VDR gene Fok1polymorphism and risk of CHD in offspring. Concerning maternal VD level and status among Egyptian healthy control mothers, they concluded that the percentage of mothers having deficient, insufficient, inadequate, and sufficient VD status were 16%, 50%, 22%, and 12%, respectively [20]. https://oamjms.eu/index.php/mjms/index In a study done by Gulenay et al aimed to evaluate maternal serum VD levels in neonates with isolated CDH compared to pregnant patients without CDH, The results showed that mean maternal serum VD levels were significantly lower in the study group than in the controls (p: 0.019) [21].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Zakazig University, Egypt by Mokhtar et al they analyzed the association between both maternal VD level and VDR gene Fok1polymorphism and risk of CHD in offspring. Concerning maternal VD level and status among Egyptian healthy control mothers, they concluded that the percentage of mothers having deficient, insufficient, inadequate, and sufficient VD status were 16%, 50%, 22%, and 12%, respectively [20]. https://oamjms.eu/index.php/mjms/index In a study done by Gulenay et al aimed to evaluate maternal serum VD levels in neonates with isolated CDH compared to pregnant patients without CDH, The results showed that mean maternal serum VD levels were significantly lower in the study group than in the controls (p: 0.019) [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, insufficient vitamin D intake often affects the endocrine pancreas and the immune system, leading to various diseases . Vitamin D deficiency is known to be associated with various diseases, such as cancer, heart disease, arterial stiffness, neuropsychiatric disorders, and diabetes . Furthermore, vitamin D has been used as an adjunct to treat COVID-19, which left more than three million people dead as of May 18, 2021 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, insufficient vitamin D intake often affects the endocrine pancreas and immune system, leading to a variety of diseases ( Arabi, Bahrami, Ranjbar, Tabesh, & Norouzy, 2020 ; Leuven, 2020 ; Wu, Cai, Liu, Zhu, & Guan, 2020 ). More recently, many studies have linked vitamin D deficiency to non-skeletal diseases, such as cancer ( Carlberg & Muñoz, 2020 ), heart disease ( Mokhtar, Fawzy, Allam, Amer, & Hamed, 2019 ), arterial stiffness ( Chen et al, 2019 ), neuropsychiatric disorders ( Kim et al, 2020 ), diabetes ( Mirzavandi et al, 2020 ; Zhang, Wu, Lu, & Fei, 2020 ) and other chronic illnesses. In addition, studies have shown that vitamin D can be used as an adjunct to the treatment of COVID-19, which ravaged the world in 2020 and left 612,054 people dead as of 6:18pm CEST, July 22, 2020 ( Annweiler, Cao, & Sabatier, 2020 ; Martín Giménez et al, 2020 ; Razdan, Singh, & Singh, 2020 ; WHO, 2020 ).…”
Section: Introductionmentioning
confidence: 99%